2008
DOI: 10.1590/s1519-69842008000400026
|View full text |Cite
|
Sign up to set email alerts
|

Infection rates of pentastomids on lizards in urban habitats in the Brazilian northeast

Abstract: The rates of pentastomid infections in the syntopic lizards Hemidactylus mabouia and Tropidurus hispidus inhabiting buildings at the Federal University of Paraiba, in João Pessoa, NE Brazil were examined. A total of 30 specimens of Hemidactylus mabouia and 55 specimens of Tropidurus hispidus were examined. The animals were sacrificed by freezing and then fixed and conserved in 70% alcohol. Analyses of the respiratory tract of Hemidactylus mabouia demonstrated that these lizards were infected by Raillietiella f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…a) All infection records for pentastomids in Brazil including this study, b) includes only studies that sampled more than 15 individuals of the same lizard species. References with number of hosts in parenthesis: Tropidurus hispidus (n = 18, Almeida et al, 2008a; n = 288, Brito et al, 2014b; n = 411, Araujo-Filho et al, 2016), T. semitaeniatus (n = 15, Almeida et al, 2008b; n = 120, Brito et al, 2014b), Micrablepharus maximiliani (n = 75, Almeida et al, 2009a), Mabuya arajara (n = 125, Ribeiro et al, 2012), M. agilis (n = 11, n = 28, Vrcibradic et al, 2002), Cnemidophorus abaetensis (n = 33, Dias et al, 2005), C. ocellifer (n = 40, Dias et al, 2005), Phyllopezus periosus (n = 6, Almeida et al, 2008b; n = 6, Brito et al, 2014b), Hemidactylus mabouia (n = 37, Anjos et al, 2007; n = 30, Almeida et al, 2008c; n = 76, Sousa et al, 2014; n = 277, Bezerra et al, 2016), P. pollicaris (n = 6, Almeida et al, 2008b; n = 22, Sousa et al, 2010; n = 94, Brito et al, 2014b; n = 132, this study) H. agrius (n = 63, this study), Gymnodactylus geckoides (n = 71, this study) and H.brasilianus (n = 24, this study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…a) All infection records for pentastomids in Brazil including this study, b) includes only studies that sampled more than 15 individuals of the same lizard species. References with number of hosts in parenthesis: Tropidurus hispidus (n = 18, Almeida et al, 2008a; n = 288, Brito et al, 2014b; n = 411, Araujo-Filho et al, 2016), T. semitaeniatus (n = 15, Almeida et al, 2008b; n = 120, Brito et al, 2014b), Micrablepharus maximiliani (n = 75, Almeida et al, 2009a), Mabuya arajara (n = 125, Ribeiro et al, 2012), M. agilis (n = 11, n = 28, Vrcibradic et al, 2002), Cnemidophorus abaetensis (n = 33, Dias et al, 2005), C. ocellifer (n = 40, Dias et al, 2005), Phyllopezus periosus (n = 6, Almeida et al, 2008b; n = 6, Brito et al, 2014b), Hemidactylus mabouia (n = 37, Anjos et al, 2007; n = 30, Almeida et al, 2008c; n = 76, Sousa et al, 2014; n = 277, Bezerra et al, 2016), P. pollicaris (n = 6, Almeida et al, 2008b; n = 22, Sousa et al, 2010; n = 94, Brito et al, 2014b; n = 132, this study) H. agrius (n = 63, this study), Gymnodactylus geckoides (n = 71, this study) and H.brasilianus (n = 24, this study).…”
Section: Resultsmentioning
confidence: 99%
“…= 0.66 %); T. semitaeniatus (n = 15, Prev = 13.3 %, Almeida et al, 2008b; n = 120, Prev = 0.51 %, Brito et al, 2014b); M. maximiliani (N = 75, Prev = 4 %, Almeida et al, 2009a), and M. arajara (n = 125, Prev = 1.6 %, Ribeiro et al, 2012). Only three studies with similar sample size (15 geckos) found a higher prevalence: H. mabouia (n = 37, Prev = 45.9 %, Anjos et al, 2007; n = 30, Prev = 20 %, Almeida et al, 2008c) and P. pollicaris (n = 22, Prev = 18.18 %, Sousa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most likely pathways by which this parasite could have been introduced to Panama are: (1) spread from adjacent infected areas, or (2) introduction to Panama via cargo (likely from Asia). Raillietiella frenata has been recorded in introduced Hemidactylus turcicus in Texas, USA (Pence and Selcer, 1988) and Hemidactylus mabouia in Brazil (Anjos et al 2007(Anjos et al , 2008Almeida et al 2008), however neither of these gecko species are established in Panama (R. Ibáñez, personal communication). If the parasite spread into Panama from either Texas or Brazil, we would expect infected toads across their entire native range (southern Texas to Brazil; Lever, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Raillietiella Vaney & Sambon, 1910 is one of the few groups of Pentastomids that infect the respiratory tract of amphisbaenids, lizards and snakes recorded in South America (Almeida et al, 2008d). Studies involving pentastomid infection in lizards in the Neotropics were recorded, mostly in Brazil: Mabuya agilis Raddi, 1823 infected larvae Raillietiella sp.…”
Section: Introductionmentioning
confidence: 99%